Implementasi Pembiayaan Musyarakah pada Usaha Mikro Kecil dan Menengah dalam Aspek Maqashid Syariah - M Taufik Hidayat; Umrotul Khasanah; Meldona (STAI Al-Mas'udiyah, 2025)
This paper examines the implementation of the musyarakah contract in Sharia-based financing for Micro, Small, and Medium Enterprises (MSMEs) through the lens of maqashid sharia. The musyarakah contract, which emphasizes the principles of justice, partnership, and blessings, aligns with Sharia principles and contributes to achieving the objectives of maqashid sharia, namely the protection of religion, life, intellect, lineage, and wealth. This form of partnership-based financing not only delivers economic benefits but also has psychological and social impacts on MSME actors, such as increased peace of mind, asset protection, and improved family welfare. This study employs a qualitative method. Data collection was conducted through in-depth interviews with Islamic financial institution managers, MSME partners, and mentoring staff, alongside participatory observation of financing activities and interactions, and examination of supporting documents such as financial reports and internal policies. The findings reveal several challenges in the field, including limited understanding of Sharia principles among MSME actors, weak financial record-keeping, and insufficient monitoring and mentoring by financial institutions. Nevertheless, the study concludes that with enhanced education, consistent mentoring, and structured supervision systems, the musyarakah contract holds significant potential in empowering MSMEs fairly and sustainably, in accordance with comprehensive Sharia objectives